Covalent Fluorination Strategies for the Surface Modification of Polydienes. Issue 11 (10th April 2017) - De Bruycker, Kevin; Delahaye, Maarten; Cools, Pieter; Winne, Johan; Prez, Filip E. Du
Abstract : Fluorinated additives bearing a reactive triazolinedione moiety are synthesized and applied for altering the wetting properties of several polydiene backbones. Both dip‐coating and reaction in solution are used to yield modified surfaces. With only 6 wt% of additive, contact angles of up to 125° can be obtained. Abstract : Nonreactive additives are widely applied to enhance polymer properties but can leach out of the material over time. In this work, two essentially different fluorinated additives bearing a triazolinedione moiety are synthesized and grafted on several polydiene backbones (acrylonitrile–butadiene–styrene, styrene–butadiene, and styrene–isoprene–styrene (SIS) copolymers), either by dip‐coating or by reaction in solution. The resulting polymers are analyzed by contact angle goniometry, size exclusion chromatography, and NMR, infrared, and X‐ray photoelectron spectroscopy. Independent of the modification procedure, the fluorophilic perfluoroalkyl additive is found at the material surface, thereby yielding a more hydrophobic surface. For SIS thermoplastic elastomers, for example, contact angles up to 125° can be obtained.